The Use of Turmeric (Extracts and Squeeze) to Detect Plaque on Teeth - Nike Haryani; Erma Mahmiyah; M. Ibraar Ayatullah (POLTEKKES KEMENKES KUPANG, 2019)
Primary school is a very strategic place for the prevention of dental and oral diseases. Delivering counseling material in learning oral health requires media. One of the media in dental and oral health education is through counseling using audio media. This audio media contains messages about dental health that are played at school every morning and can be exposed and heard every day so elementary school children can behave well in dental health. This study aims to determine the effectiveness of audio media outreach programs to the knowledge and level of dental and mouth hygiene of students at State Primary School 26 Kalimas Tengah, Kubu Raya Regency in 2019. This study was a quasi-experimental study with a Pre-Post observation research design. The samples of this study were 68 people which were class III, IV and V. The results showed the average rank of knowledge index before counseling with audio media was 8.928 and p was 0.020 (p<0.05) with index of dental and oral hygiene level was 0,00 and p of 0,000 (p<0.05). Meanwhile, after counseling with audio media was 9,500 and p of 0.020 (p<0.05) with a level of dental and oral hygiene of 35.00 and p of 0,000 (p<0,05). The conclusion of this study is counseling with audio media is more effective in increasing knowledge which can improve oral and dental hygiene